One-pot cascade synthesis of 2-cyanoacrylamides via Sn-catalyzed acetic acid free selective monohydration of dinitrile - Shaikh, Taufeekaslam M. Y.; Mulla, Shafeek A. R. (ChemistrySelect, 2018)
The simple, mild, novel and an efficient new protocol has been developed for the straightforward synthesis of 2-cyanoacrylamides. This is the first report in which Sn-catalyzed acetic acid free selective monohydration of dinitrile was achieved for a one pot cascade synthesis of 2-cyanoacrylamides in good to excellent yield via condensation of various aldehydes, heterocyclic aldehydes with malononitrile.
Keywords: 2-cyanoacrylamides; Aldehyde; one pot; SnCl2 center dot 2H(2)O